2017
DOI: 10.1371/journal.pone.0180128
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of glaucoma-related features within the optic nerve head using enhanced depth imaging optical coherence tomography

Abstract: Structural differences between optic nerve head (ONH) parameters in glaucomatous and non-glaucomatous eyes has been documented, however the association between such parameters in patients with different disease stages is yet to be elucidated. We investigated the relationship between different laminar and prelaminar ONH structures using enhanced depth imaging spectral-domain optical coherence tomography (EDI OCT) in a population with and without glaucoma. In this observational case-control study, we prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
1
15
0
1
Order By: Relevance
“…Even though these parameters differed significantly between glaucomatous eyes and controls, we did not find any significant structure-functional correlation between LC-derived parameters and VFI values. Our comparative laminar findings are in agreement with most previously published data, as it has been shown that glaucomatous eyes present thinner and deeper LCs than controls [10, 16]. In addition, our structure-functional findings on LC depth corroborate those from Park et al [31], as the authors did not find a significant association between ALD and VFMD values in eyes with different stages of treated glaucoma.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Even though these parameters differed significantly between glaucomatous eyes and controls, we did not find any significant structure-functional correlation between LC-derived parameters and VFI values. Our comparative laminar findings are in agreement with most previously published data, as it has been shown that glaucomatous eyes present thinner and deeper LCs than controls [10, 16]. In addition, our structure-functional findings on LC depth corroborate those from Park et al [31], as the authors did not find a significant association between ALD and VFMD values in eyes with different stages of treated glaucoma.…”
Section: Discussionsupporting
confidence: 93%
“…We adopted the same glaucoma definition we used in previous studies from our group [10–12]. In brief, characteristic glaucomatous optic neuropathy was defined as a vertical cup-to-disc ratio (VCDR) of 0.6 or greater, asymmetry of VCDR of 0.2 or greater between eyes, presence of localized or diffuse peripapillary RNFL (pRNFL) defects, or neuroretinal rim defects in the absence of any other abnormalities that could explain such findings [10–12].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 OCT images of eyes with POAG have shown lamina cribrosa deformations such as increased anterior lamina cribrosa depth (ALCD) and decreased lamina cribrosa thickness (LCT). [10][11][12] Diabetes mellitus (DM) is a systemic disease characterized by hyperglycaemia secondary to insulin deficiency or insulin resistance. Increased apoptosis of RGCs and early RGC death have been reported in diabetic eyes.…”
Section: Introductionmentioning
confidence: 99%